Increased case‐finding and uptake of direct‐acting antiviral treatment essential for micro‐elimination of hepatitis C among people living with HIV: a national record linkage study. Issue 5 (17th December 2020) - McLeod, A; Hutchinson, SJ; Smith, S; Leen, C; Clifford, S; McAuley, A; Wallace, LA; Barclay, ST; Bramley, P; Dillon, JF; Fraser, A; Gunson, RN; et al.
Abstract : Objectives: Micro‐elimination of hepatitis C virus (HCV) in people living with HIV (PLHIV) and co‐infected with HCV has been proposed as a key contribution to the overall goal of HCV elimination. While other studies have examined micro‐elimination in HIV‐treated cohorts, few have considered HCV micro‐elimination among those not treated for HIV or at a national level. Methods: Through data linkage of national and sentinel surveillance data, we examined the extent of HCV testing, diagnosis and treatment among a cohort of PLHIV in Scotland identified through the national database of HIV‐diagnosed individuals, up to the end of 2017. Results: Of 5018 PLHIV, an estimated 797 (15%) had never been tested for HCV and 70 (9%) of these had undiagnosed chronic HCV. The odds of never having been tested for HCV were the highest in those not on HIV treatment [adjusted odds ratio (aOR) = 7.21, 95% confidence interval (CI): 5.15–10.10). Overall HCV antibody positivity was 11%, and it was at its highest among people who inject drugs (49%). Most of those with chronic HCV (91%) had attended an HCV treatment clinic but only half had been successfully treated (54% for those on HIV treatment, 12% for those not) by the end of 2017. The odds of never having been treated for HCV were the highest in those not on HIV treatment (aOR = 3.60, 95% CI: 1.59–8.15). Conclusions: Our data demonstrate that micro‐elimination of HCV in PLHIV is achievable but progress will require increased effort to engage and treat those co‐infected, including those not being treated for their HIV.